تعليم كتاب الأجرومية للطلاب في الفصل التاسع من المدرسة المتوسطة الإسلامية بسوكوهرجو فيليماهن كديري - Riza, Ahmad Rifa’i; Faruq, Umar; Khamidah, Nur (Program Studi Pendidikan Bahasa Arab, 2024)
Learning Arabic is a learning that most people consider difficult, because Arabic is inseparable from the science of nahwu. And the basis of nahwu knowledge that is commonly used by Islamic boarding schools is the book of Jurumiyah, because the book is considered the simplest and easiest to explain and usually the learning of the book of Jurumiyah is carried out in Islamic boarding schools but this is done in madrasas or formal institutions, and every learning must have advantages and disadvantages, one of which is in the study of the book of Jurumiyah. The formulation of this research problem is how the learning process of the book of jurumiyyah for grade 9 students at Mts Islamiyah Sukoharjo Plemahan Kediri, as well as the advantages and disadvantages of learning the book of Jurumiyah for grade 9 students at Mts Islamiyah Sukoharjo Plemahan Kediri. This study uses a qualitative research approach that is descriptive. Research Place at Madrasah Tsanawiyah, grade 9 students at Mts Islamiyah Sukoharjo Plemahan Kediri. The data sources came from the school principal, the teacher of the teacher, the Arabic teacher and the 9th grade students. The method of data collection uses observation, interviews and documentation. The results of the research on the study of the book of jurumiyah for grade 9 students at Mts Islamiyah Sukoharjo Plemahan Kediri have the goal of providing students with a basic understanding of the rules of nahwu used in Arabic, in the learning of the book of Jurumiyah the teacher uses the bandongan method. As for the reason for using this jurumiyah book because this book is the most famous book in all circles and the easiest for beginners or beginners, this jurumiyah learning is carried out 1 time for 1 week and has been included in the madrasah curriculum. Meanwhile, the advantages in the learning process of the book of Jurumiyah students are able to understand qowaid correctly. And the shortcomings in the learning process of the book of Jurumiyah are that the material taught focuses on qowaid so that students do not delve too deeply when learning Arabic.